No Substitute for Victory - Hosted by John Wayne - Slatzer, Robert F. (United States : Alaska Pictures Productions, 1970)
Who better than John Wayne to host this documentary look at "America's fight against Communist aggression" in Vietnam? Along with a history of Red atrocities from the Russian Revolution to Southeast Asia, Wayne talks with such notables as Martha Raye, newsman Lowell Thomas and Green Beret-turned-pop star Sgt. Barry Sadler. In the end Wayne a puts the blame for the war's dragging on squarely on the shoulders of a "hostile press." The documentary aimed to shift the opinion of the public to favor support of the U. S. war against North Vietnam and the Viet Cong during a time when America's cultural atmosphere was strongly antagonistic towards this country's involvement. The documentary also contains archival footage related to both the Vietnam conflict and the history of the establishment of Communist regimes; however, their discursive framing is misleadingly created.
Duration: 01:10:00
Keywords: Documentary films